PENGARUH KEPEMIMPINAN DAN PENGAWASAN TERHADAP DISIPLIN KERJA KARYAWAN DI PT GOLDEN BLOSSOM SUMATRA (GBS) - Yuki Nuryadi; M Kurniawan; Reina Damayanti (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This study aims to test the influence of Leadership and Supervision on employee Work Discipline at PT Golden Blossom Sumatra (GBS). The population of this study included 181 employees at PT Golden Blossom Sumatra (GBS), the sample drawn was 108 respondents with a proportionate stratified random sampling technique. The finding concludes that Leadership has a positive and significant effect on employee Work Discipline, Supervision has a positive and significant effect on employee Work Discipline and Leadership and Supervision simultaneously have a positive and significant effect on employee Work Discipline at PT Golden Blossom Sumatra (GBS). The contribution of Leadership and Supervision influence on the Work Discipline of workers at PT Golden Blossom Sumatra (GBS) was 76.7% while the remaining 23.3% is explained by various factors excluded from this study. Keywords: Leadership; Supervision; Work Discipline